Evaluating the Age Distribution of Exposed Crust in the Acasta Gneiss Complex Using Detrital Zircons in Pleistocene Eskers. (6th May 2022) - Bilak, Grayson S.; Niemetz, Kaylyn; Reimink, Jesse R.; Reyes, Alberto V.; Chacko, Thomas; DuFrane, S. Andrew; Belosevic, Michael; Ketchum, John W. F.
Abstract: The Acasta Gneiss Complex (AGC) is a ∼2, 400 km 2 Hadean‐Mesoarchean terrane that contains the oldest known zircon‐bearing rocks on Earth. Despite its importance for early Earth geology, only a small fraction (∼50 km 2 ) of the AGC has been mapped in detail. We use detrital zircon grains from late Pleistocene eskers that transect the Complex to approximate the lateral extent and relative proportions of diverse‐aged ancient rock units within the vast, little‐studied parts of the AGC. The esker sediment was derived from glacially eroded bedrock and therefore zircon grains can serve as a proxy for the ages of exposed bedrock in the study area. U‐Pb dates on ∼2400 detrital zircons from coarse and fine grain‐size fractions along the esker transect yield age distributions that coincide with ages of regionally mapped AGC bedrock, the adjacent Wopmay Orogen, and granitoids of the Slave craton. Based on detrital zircon age distributions and new reconnaissance‐scale mapping, we infer that 3.37 Ga granitoids are a volumetrically significant component of the unmapped AGC. Esker zircons older than 3.7 Ga are present in most esker samples but at low abundance, which suggests that Eoarchean and Hadean rocks are a volumetrically subordinate component of the AGC. However, the data also suggest that unmapped rocks at least as old as 3.95 Ga are present toward the inferred eastern limit of the AGC, a location where Eoarchean rocks have not been recognized previously. Plain Language Summary: The Acasta Gneiss Complex is a small region of bedrock in the Northwest Territories, Canada, which contains the oldest precisely dated rocks currently known on Earth (4.02 billion years old). The study of this area is crucial to understanding how terrestrial crust first formed on our planet. Despite its significance, the region is poorly mapped with the exception of the initial discovery site. To overcome these difficulties, we sampled glacial sediment (sand and gravel) derived from local bedrock during glaciation, then extracted and dated zircon crystals to estimate relative proportions of diversely‐aged bedrock in the area. Our findings indicate the majority of unmapped bedrock is roughly 3.37 billion years old. Our findings also indicate that small vestiges of bedrock as old as 3.95 billion years old remain yet to be discovered in the unmapped area east of the region. Key Points: U‐Pb dates from detrital zircons indicate that a large area of the Acasta Gneiss Complex (AGC) is underlain by 3.37 billion years old granite The provenance of glacially derived sediment in the western Slave craton indicate a transport distance of less than 50 km Detrital zircons older than 3.9 billion years indicate presence of ancient crust up‐ice from the few mapped AGC outcrops